Students’ voices on academic writing in higher education: Needs, preferences, and digital integration - Yanuarti Apsari; Nur Hidayanto Pancoro Setyo Putro; Dyah Setyowati Ciptaningrum (Jurnal Profesi Pendidikan, 2026)
Academic writing is a crucial skill for students in higher education; however, it remains a significant challenge, particularly in English as a Foreign Language (EFL) contexts. Limited research has foregrounded students’ voices regarding their academic writing needs, learning preferences, and the role of digital tools in supporting their writing development. Addressing this gap, the present study aims to explore students’ perceptions of their academic writing needs, investigate their preferred ways of learning academic writing, and examine their perceptions of the role of digital tools in facilitating and supporting their writing processes. This study employed a descriptive qualitative design to investigate students’ experiences and perceptions of academic writing. Data were collected through a survey involving 82 university students and in-depth interviews with six selected participants. The collected data were analyzed using thematic analysis. The findings show that students struggle with writing coherent paragraphs and structuring arguments. To overcome these challenges, they prefer a combination of structured scaffolding and digital collaborative learning. Regarding digital tools, research databases and writing platforms were the most commonly used, with Google Scholar used for reference searching and Grammarly for writing support. Moreover, students preferred interactive media, particularly educational videos, digital mind-mapping tools, and interactive quizzes. These findings suggest that integrating structured instruction, collaboration, and interactive digital tools can improve students’ engagement and academic writing skills.